Biocompatible copolymer formulations to treat glioblastoma multiforme. - Gobbo, Oliviero (My University, 2021)
The treatment for glioblastoma multiforme (GBM) has not changed for more than 20 years while the prognosis for the patients is still poor and most of them survive less than 1 year after diagnosis. The standard of care for GBM is comprised of surgical resection followed by radiotherapy and oral chemotherapy with temozolomide. The placement of carmustine wafers in the brain after tumour removal is added in cases of recurrent glioma. Significant research is underway to improve the GBM therapy outcome and patient quality of life. Biomaterials are in the front line of the research focus for new treatment options. Specially, biocompatible polymers have been proposed in hydrogel-based formulations aiming at injectable and localized therapies. These formulations can comprise many different pharmacological agents such as chemotherapeutic drugs, nanoparticles, cells, nucleic acids, and diagnostic agents. In this manuscript, we review the most recent formulations developed and tested both in vitro and in vivo using different types of hydrogels. Firstly, we describe three common types of thermo-responsive polymers addressing the advantages and drawbacks of their formulations. Then, we focus on formulations specifically developed for GBM treatment.
Keywords: Glioblastoma multiforme; Injectable hydrogels; Nanoparticles; Chemotherapy; Thermo-responsive polymers; Cancer; Nanoscience & Materials; DRUG DELIVERY SYSTEMS; NanoMedicine; brain cancer; precision nanomedicine; Health